Efektivitas Penggunaan Kredit Usaha Terhadap Produktivitas UKM dan Pendapatan UKM Anggota Koperasi di Kelurahan Padangsambian, Kecamatan Denpasar Barat, Provinsi Bali - I Wayan Chandra Adyatma; Made Dwi Harmana (Lembaga Penelitian, Universitas Warmadewa, 2020)
The purpose of this research is to determine the effectiveness of credits on the SMEs productivity and the income of cooperative members' SMEs in Padangsambian Village. The analytical tool that used on this research is the SEM analysis of Partial Least Square (PLS). This study uses primary data conducted by distributing questionnaires to SMEs that borrow business loans on the Padangsambian Village as many as 100 respondents. The results of the research analysis test show (i) The effectiveness of the use of business credit has a positive and significant effect on the productivity of SMEs in Padangsambian Village. (ii) Productivity of SMEs has a positive and significant effect on the income of SMEs in Padangsambian Village. (iii) The effectiveness of the use of SME business credit in Padangsambian Village has a positive and significant effect on the income of SMEs in Padangsambian Village through the productivity of the UKM.